Autism Spectrum Disorder (ASD) Law in Chile - Salum Tomé, José Manuel (Advances in Social Sciences Research Journal, 2025)
The TEA Law guarantees the right to equal opportunities and safeguards the social inclusion of children, adolescents, and adults with ASD, eliminating all forms of discrimination. It promotes a comprehensive approach in the social, health, and educational spheres and raises awareness about this issue. The law is based on fundamental principles such as dignified treatment, progressive autonomy, a gender perspective, intersectionality, participation and social dialogue, early detection, ongoing monitoring, and neurodiversity.